Effects of Public Service Quality, Performance Effectiveness and Professionalism Work on Community Satisfaction at Badan Perencanaan Pembangunan Daerah Kota Bandung - Juju Zuhriatusobah H.S; Eva Hardiana (Enrichment : Journal of Management, 2021)
This research moved from the problems that showed dissatisfaction with the community which was allegedly influenced by the quality of service, the effectiveness of the work and professionalism of work at Badan Perencanaan Pembangunan Daerah Kota Bandung. Bappeda has not been able to serve the community well seen from the relatively long time efficiency in serving the community, there are complaints from the public regarding employee performance and performance targets that have not all been realized. The purpose of this study was to determine the magnitude of the influence of public services, the effectiveness of performance and professionalism of work partially and simultaneously on community satisfaction at Badan Perencanaan Pembangunan Daerah Kota Bandung. The research method used is a quantitative method with an associative approach and descriptive verification analysis. The technique of collecting data through questionnaires distributed to employees of Badan Perencanaan Pembangunan Daerah Kota Bandung was 93 respondents. To determine how much influence public service has, the effectiveness of performance and work professionalism uses the t test and F test with the SPSS version 22 program. Based on the results of testing that the influence of the quality of public services on community satisfaction is 39.5%, the effect of performance effectiveness on community satisfaction is 27.1%, the effect of work professionalism on community satisfaction is 40.8%, while the effect of quality public services, performance effectiveness and simultaneous work professionalism towards community satisfaction is 64.1% and the rest is influenced by other variables not examined by the researcher.